1987
DOI: 10.1007/bf00326554
|View full text |Cite
|
Sign up to set email alerts
|

The promoter proximal region in the virD locus of Agrobacterium tumefaciens is necessary for the plant-inducible circularization of T-DNA

Abstract: The formation of crown gall tumours involves the transfer of the T-DNA region of the Ti plasmid from Agrobacterium to plant cells and its subsequent integration into plant chromosomes. When agrobacteria are incubated with plant protoplasts or exudates of plants, the T-DNA region is circularized by recombination or cleavage and rejoining between the 25 bp terminal repeats; the formation of circular T-DNAs is thought to be one step in T-DNA transfer (Koukolikova-Nicola et al. 1985; Machida et al. 1986). We previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
18
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…One model for T-DNA processing is that initial border sequence cleavage by the virD endonuclease is followed by a replication event, which results in replacement synthesis of the bottom strand of T-DNA and the concomitant displacement of a T-strand molecule (1,44). However, the structure of T-DNA molecules transferred into plant cells is not yet clearly established, since doublestranded linear (23,49) and circular (2,29,54) T-DNA molecules also have been identified as products of the cleavage reaction.…”
mentioning
confidence: 99%
“…One model for T-DNA processing is that initial border sequence cleavage by the virD endonuclease is followed by a replication event, which results in replacement synthesis of the bottom strand of T-DNA and the concomitant displacement of a T-strand molecule (1,44). However, the structure of T-DNA molecules transferred into plant cells is not yet clearly established, since doublestranded linear (23,49) and circular (2,29,54) T-DNA molecules also have been identified as products of the cleavage reaction.…”
mentioning
confidence: 99%
“…This gene presumably encodes a transcriptional activator that induces its own expression and the expression of the genes 1i'rB, virC, virD, virE, and pinF (27,42,51). The virD locus encodes a T-DNA border-specific endonuclease (1,17,41,49,52,53) that nicks the T-DNA border repeat sequences on the bottom strand, generating single-stranded T-DNA molecules called T-strands (1,40,48). T-strands can be coated with a virE-encoded singlestranded-DNA-binding protein (6,8,11,15) and have been hypothesized to be the form of the T-DNA transferred to the plant cell (43).…”
mentioning
confidence: 99%
“…Several potential intermediates in T-DNA transmission accumulate in A. tumefaciens after induction of the vir genes. Various groups have reported the generation of circular forms of the T-DNA (2,17,20,49). Induction ofA.…”
mentioning
confidence: 99%
“…Recently, we reported that double-stranded cleavages occur at each of the T-DNA borders upon cocultivation of A. tumefaciens with regenerating tobacco protoplasts (43). All of these different reactions require virA, virG, and the first two open reading frames of the virD locus (2,13,37,43,49,50).…”
mentioning
confidence: 99%